PEDAGOGICAL DIAGNOSTIC OF CONFLICTS ARISING IN THE PROCESS OF HIGHER EDUCATION BASED ON MODERN APPROACHES (Scientific journal of the Fergana State University, 2023)
In this article, the author studied pedagogical conflicts as a phenomenon that occurs in the learning process, revealed the causes of pedagogical conflicts and conflict situations that arise in universities from the point of view of pedagogy. Conflict situations in universities and the nature of conflicts, conflicts of interest, participation of the head of the university, teachers, students and parents in the occurrence of conflicts in the educational process are described. The content of the conflict, duration, levels of contradictions that form the basis of the conflict, the time of the conflict, the content of the joint activities of the participants, the psychological characteristics of the conflict situation, the types of conflicts according to the degree of their manifestation. As a result of the analysis of the works of domestic and foreign researchers, a definition of the concepts of pedagogical conflict and conflict situation has been developed. A complete list of conflict situations and conflict-generating behavior among students of higher educational institutions is given and their classification is given. As a result of the analysis, from the point of view of pedagogy, very complex and delicate conflict situations that arise among students of higher educational institutions, it is proposed to use modern approaches to identifying the reasons that guarantee their effective management.